Islamic Constitutionalism Values: A Study of al-Muqaddimah fi Intizam Waza'if al Malik, Tsamarat al Muhimmah Diyafah Li al Umara Wa al Kubara' Ahl Hakim and Gurindam Dua Belas Raja Ali Haji - Sibarani, Hos Arie Rhamadan; Umar, M. Hasbi; Hidayati, Rahmi (PT. Riset Press International, 2025)
This study explores the values of Islamic constitutionalism as reflected in three significant texts: al-Muqaddimah fi Intizam Waza’if al-Malik, Tsamarat al-Muhimmah Diyafah Li al-Umara wa al-Kubara' Ahl Hakim, and Gurindam Dua Belas by Raja Ali Haji. These works, originating from diverse socio-cultural contexts, represent a continuum of Islamic political thought that emphasizes justice (‘adl), consultation (shūrā), accountability (mas’ūliyyah), and the ethical limitations of political authority. The study aims to examine how these texts articulate principles of governance consistent with Islamic constitutional ideals and how such principles remain relevant to contemporary constitutional discourse. Using a qualitative-descriptive method, this research analyzes the textual content of each work through the lens of Islamic political ethics and compares their constitutional implications. Findings show that each text, despite its distinct genre and historical setting, upholds a model of leadership that is morally bound, consultative, and justice-oriented. al-Muqaddimah offers a structured political theory rooted in classical Islamic governance, Tsamarat al-Muhimmah emphasizes the moral character and restraint of leaders, while Gurindam Dua Belas integrates Islamic and Malay ethical-political teachings through literary expression. The study concludes that these texts provide a foundational framework for understanding Islamic constitutionalism beyond legal formalism, focusing on the moral obligations of rulers and the collective rights of society. This research contributes to the discourse on Islamic constitutional theory by highlighting the ethical and cultural dimensions of Islamic governance embedded in classical and local intellectual traditions.